Stabilization On Expansive Soil For Road-Subgrade For Geotechnic Disaster Approach - Munirwansyah Munirwansyah; Reza Pahlevi Munirwan (International Journal of Disaster Management, 2017)
This research was conducted for Blang Dalam expansive clay is located in Pidie Jaya-Aceh, Sumatra-Indonesia, which is one of the embankment material used as road subgrade. Road construction use expansive clay soil for subgrade experiencing many damages. The damage of road construction is caused by low bearing capacity when water levels change, high soil plasticity results swelling experience and shrinkage during the rainy and dry season respectively. One method of expansive clay stabilization effort to increase the carrying capacity of the soil is a mixture of Lime Ca (OH)2. Lime mix percentage variation are; 3%, 6%, 9% and 12% of the dry weight of soil. The purpose of this research is to determine the effect of lime a stabilizing agent to the improvement of the physical and mechanical properties of expansive soil. The result of untreated soil for free swelling is 1.141 % and swelling pressure of 23.18 kPa. For treated soil-lime mixture of 3%, 6%, 9% and 12%, the free swelling value are 0.64 %, 0.47 %, 0.40 % and 0.23 % respectively. Moreover, swelling pressure values for lime variation of 3%, 6%, 9% and 12% are 15.44 kPa, 13.25 kPa, 10.51 kPa, and 9.79 kPa respectively. 12% of soil-lime results shows the most effective results of free swelling which decrease for 1.14% of untreated soil to 0.23% and swelling pressure value of 23.18 kPa for untreated soil decline to  9.79 kPa.